Deformacijska analiza po postopku Delft - Marjetič, Aleš (Geodetski vestnik, 2012)
The Delft approach, a method for the deformation analysis, is presented in this article. Based on geodetic measurements, the statistical significance of displacements at the surface is determined with statistical methods. A numerical example shows the effectiveness of the presented method.
Keywords: deformacijska analiza; deformation analysis; Delft approach; numerical example; postopek Delft; računski primer